Role of regional cooperation and integration in resolving energy insecurity in South Asia - Sarkar, Tapan; Hossain, Shanawez; Islam, K. M. Nazmul (Asian Development Bank Institute, 2022)
This book chapter was published in the book named Energy Insecurity in Asia Challenges, Solutions, and Renewable Energy and the definite version is available at : https://www.adb.org/publications/role-regional-cooperation-integration-improving-energy-insecurity-south-asia